Abnormalities of right ventricular long axis function after atrial repair of transposition of the great arteries. Issue 2 (1st August 2001) - Derrick, G P; Josen, M; Vogel, M; Henein, M Y; Shinebourne, E A; Redington, A N
Abstract : BACKGROUND: While volume derived global indices of right ventricle (RV) function are frequently abnormal after the Mustard procedure, the mechanism for these abnormalities is poorly understood. RV muscle fibres are predominantly arranged longitudinally and thus indices derived in the long axis may better describe RV function. METHODS: 20 survivors of the Mustard operation were studied (age 7.8–37.3 years, median 14.2 years). Long axis recordings from the apical four chamber view were obtained with the M mode cursor positioned through the lateral angle of the tricuspid valve annulus. M mode traces were recorded on paper and later digitised to derive total atrioventricular ring excursion, peak lengthening rate, and peak shortening rate. These data were averaged and compared with control data for the normal RV and left ventricle (LV). RESULTS: RV total atrioventricular ring excursion was lower than that for the RV (p < 0.0001) or LV (p < 0.005) of controls. Peak lengthening rate was lower than the normal RV (p < 0.0001) and LV (p < 0.0001) rates. Furthermore, peak shortening rate was less than that of normal RV (p < 0.0001) and normal LV (p < 0.005) controls. CONCLUSION: Systemic RV long axis function is notably reduced compared with that of either the normal subpulmonary RV or the systemic LV. This presumably reflects the response of the predominantly longitudinally arranged myocardial fibres to increased afterload. However, such measurements may provide a more sensitive marker for progressive changes in global function during long term follow up.